Work in Progress: Inculcating Empathy through Team-Based Problem Solving in Cooperative Problem Based Learning Classroom - Mohd Yusof, Khairiyah; Jumari, Nur Fazirah; Samsuri, Nur Shahira; Tengku Malim Busu, Tengku Nur Zulaikha (Semarak International Journal of STEM Education, 2024)
The role of empathy as a major part of emotional intelligence is widely explored in engineering education research. Despite numbers of research on empathy development during classroom, the link between empathy and cooperative problem-based learning classroom are not highlighted. Thus, in this paper, an attempt of first step in covering this gap emphasis on the qualitative data of their reflective thinking towards their difficulties in solving the problem and seeking help. The right meaning of empathy in the context of team working is developed and conceptual framework based on social learning theory for future qualitative method was presented.